Differences in Population Characteristics and Modeled Response to Harvest Regulations in Reestablished Appalachian Walleye Populations. (15th January 2022) - Smith, Dustin M.; Hilling, Corbin D.; Welsh, Stuart A.; Wellman, David I.
Abstract: Historically, the Monongahela, Tygart, and Cheat River watersheds in West Virginia were impaired by acidification from acid mine drainage and Walleye Sander vitreus were extirpated from these watersheds by the 1940s. Walleye were reestablished after water quality improvements following passage of environmental legislation and subsequent reintroduction efforts. We compared population characteristics, with emphasis on growth, of Walleye and used modeling to predict the potential effects of harvest regulations in the Monongahela River and two main‐stem reservoirs in the Cheat River and Tygart River watersheds. Statistical comparisons of von Bertalanffy growth curves and relative growth indices indicated that Walleye growth significantly differed across all water bodies. Relative growth index results suggested that Walleye growth was above average in Cheat Lake, average in the Monongahela River, and below average in Tygart Lake relative to other North American populations. Growth was negatively correlated with Walleye relative abundance and positively correlated with estimates of productivity (total phosphorus, chlorophyll a ). Walleye diets significantly differed across all water bodies, with diets dominated by Yellow Perch Perca flavescens and Gizzard Shad Dorosoma cepedianum in Cheat Lake, where growth was fastest. Population modeling suggested that effects of exploitation on yield, spawning potential, and size structure were similar under regulations of no length limit and a minimum length limit (381 mm). Models suggested that removing length limits in Tygart Lake could increase angler harvest opportunities and pose minimal threat to the fishery. Models suggested that a protected slot limit could provide increased protection to the spawning potential of Cheat Lake and the Monongahela River populations. Additionally, models predicted that a protected slot limit could increase the number of large (>630‐mm) Walleye in these waters. Our findings demonstrate the different characteristics that Walleye populations can develop after reestablishment based on abiotic and biotic conditions and the need for watershed‐specific management.